A Review on Sociocultural Barriers Affecting Healthcare Access Among Older Adults in Nigeria: Review Article (Journal of Pharma Insights and Research, 2025)
Nigeria faces significant demographic changes with a projected increase in adults aged 60 and above from 6% in 2024 to over 30 million by 2050. The healthcare system shows substantial gaps in meeting the special medical needs of older adults, particularly in dental and general health services. A systematic analysis of literature from major databases including PubMed, Scopus, Web of Science, African Journals Online, and Google Scholar revealed several barriers affecting healthcare access. Economic constraints were identified as primary obstacles, with over 70% of health expenditure coming from out-of-pocket payments. Geographic disparities between urban and rural areas compound access difficulties, while infrastructural limitations and workforce shortages further restrict service delivery. Sociocultural factors, including traditional beliefs and gender dynamics, significantly influence health-seeking behaviors. This review identifies critical policy gaps, notably the exclusion of older adults from national health insurance schemes and the marginal integration of dental services into primary healthcare. The results indicate an urgent need for age-responsive health policies, expanded insurance coverage, and strengthened primary care systems. Implementing targeted interventions addressing both general and dental healthcare needs while considering socioeconomic and cultural contexts could significantly improve health outcomes among Nigeria's aging population